Eating patterns and prevalence of obesity. Lessons learned from the Malaysian Food Barometer. (1st December 2016) - Fournier, T.; Tibère, L.; Laporte, C.; Mognard, E.; Ismail, M.N.; Sharif, S.P.; Poulain, J.-P.
Abstract: The Malaysian society is experiencing and coping with a fast modernization process, which is characterized by a rapid urbanization and rural exodus, an important reduction of the size of households, and the emergence of a new middle class. The Malaysian Food Barometer launched in 2013 has provided better understanding how these macro issues have affected the lifestyles and especially the food habits of the Malaysians. The country has indeed undergone a transition period from under-nutrition to over-nutrition in a few decades, with the prevalence of overweight and obesity having markedly and rapidly increased. A quantitative survey (n = 2000), elaborated from a qualitative preliminary phase, was carried out with the aim of analyzing the transformation of food habits at the national level. The present article focuses on the BMI issue in Malaysia, and investigates its relationships with the socio-demographic variables of the population, as well as their eating patterns. The mean BMI is 23.64 kg/m 2, with 9.5% of the sample being obese, and 22% overweight. Strong statistical associations have been identified between BMI and independent variables such as size of the living area, ethnicity, level of education, gender, and age. Contrary to general believe, overweight and obesity were neither associated with the number of food intakes taken per day (including snacks) nor with the frequency of eating out. Nonetheless, obesity is over-represented in people who have dissonant eating behaviors, i.e. who declare having fewer food intakes a day (food norms) than they do actually (food practices). This process testifies that the Malaysians are experiencing a "food transition", which is linked with socio-economic development.